Model Pembelajaran Problem-Based Learning : Implementasi pada Pembelajaran Biologi Materi Sistem Gerak - Melisa Paulina Moonik; Anatje Lihiang; Christny F.E. Rompas (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research aims to improve student learning outcomes in motion system materials by applying the Problem-Based Learning (PBL) learning model at Tumou Tou Girian Christian High School, Bitung. This research was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The first cycle showed that only 36% of students completed learning, while the other 64% did not. In the second cycle, student learning completeness increased to 84% after improvements and the implementation of more effective strategies. Applying PBL allows students to actively engage in learning, develop problem-solving skills, and think critically. The results of this study show that PBL can increase students' motivation in learning and encourage better interaction between students. Additionally, the PBL model is effective in helping students construct their knowledge, relate the subject matter to real life, and improve their overall learning outcomes. This research contributes to developing innovative learning methods that can be applied to improve the quality of education, especially in biology learning. These findings imply the importance of using problem-based learning models in improving education quality and students' high-level thinking skills. For further research, exploring the application of PBL in other subjects and its impact on students' social skills is recommended.